To check the Mma result (which is not absolutely straightforwardly here) let us first get the indefinite integral:
Integrate[(1 - Exp[α (s - T)])*Exp[α (t - s)], s,
Assumptions -> {α > 0, 0 <= t <= T, T > 0, t > 0}] //
Simplify[#, {α > 0, 0 <= t <= T, T > 0, t > 0}] &
(* -((E^((-s + t) α) + E^((t - T) α) s α)/α) *)
To better visualize it I show also the image:
Let us make sure that it is right:
D[-((E^((-s + t) α) +
E^((t - T) α) s α)/α), s] //
Simplify[#, {α > 0, 0 <= t <= T, T > 0, t > 0}] &
(* E^((-s + t) α) - E^((t - T) α) *)
which is equal to your original function:
(1 - Exp[α (s - T)])*Exp[α (t - s)] //
Simplify[#, {α > 0, 0 <= t <= T, T > 0, t > 0}] &
(* E^((-s + t) α) - E^((t - T) α) *)
Now, let us apply the Newton-Leibnitz theorem directly:
(-((E^((-s + t) α) +
E^((t - T) α) s α)/α) /.
s -> T) - (-((
E^((-s + t) α) +
E^((t - T) α) s α)/α) /. s -> t) //
Simplify[#, {α > 0, 0 <= t <= T, T > 0, t > 0}] &
(* (1 + E^((t - T) α) (-1 + t α - T α))/α *)
You can make sure that the result is equal to that obtained by Mma for the definite integral
Integrate[(1 - Exp[α (s - T)])*Exp[α (t - s)], {s, t,
T}, Assumptions -> {α > 0, 0 <= t <= T, T > 0, t > 0}] //
Simplify[#, {α > 0, 0 <= t <= T, T > 0, t > 0}] &
(* (1 + E^((t - T) α) (-1 + t α - T α))/α *)
Thus, as @Nasser wrote in his comment, Mma gives the right result.
Have fun!